Elevated haemoglobin A1c but not fasting plasma glucose conveys risk of chronic kidney disease in non-diabetic individuals. (December 2018) - Koshi, Tomomichi; Sagesaka, Hiroyuki; Sato, Yuka; Hirabayashi, Kazuko; Koike, Hideo; Yamauchi, Keishi; Nishimura, Rimei; Noda, Mitsuhiko; Yamashita, Koh; Aizawa, Toru
Highlights: In non-diabetic people, high HbA1c, not FPG, is an independent risk for incident CKD. Prediabetes diagnosed by elevated HbA1c but not FPG is an independent risk for CKD. Elevated HbA1c but not FPG is a conveyer of CKD risk at the stage of prediabetes. Abstract: Aims: To compare impact of elevated HbA1c and fasting plasma glucose (FPG) on incident chronic kidney disease (CKD) in a non-diabetic cohort. Methods: Data from diabetes- and CKD-free 25, 109 health examinees were retrospectively analysed with a mean observation period of 5.3 years. Prediabetes was diagnosed by the ADA and WHO criteria, and CKD by estimated glomerular filtration rate (eGFR) < 60 ml/min/1.73 m 2 and/or dipstick proteinuria. Cox proportional hazards model was applied with sex, age, insulin sensitivity, systolic blood pressure, eGFR and serum alanine aminotransferase level as covariates. Results: For incident CKD (n = 2483), high HbA1c but not FPG was an independent risk: adjusted hazard ratio (AHR, 95%CI) for HbA1c 1% and FPG 1 mmol/L, 1.91 (1.70–2.16) and 0.85 (0.60–1.20), respectively. Prediabetes by the ADA and WHO criteria were both risk for CKD with AHR (95%CI), 1.21 (1.12–1.32) and 1.31 (1.16–1.48), respectively. Prediabetes diagnosed by 'elevated HbA1c irrespective of FPG', either by the ADA and the WHO definition, was a risk with AHR (95%CI), 1.48 (1.36–1.61) and 1.51 (1.31–1.74), respectively. In contrast, prediabetes diagnosed by 'raised FPG irrespective of HbA1c' was not a CKD risk. Conclusions: Elevated HbA1c, but not FPG, identified CKD risk in non-diabetic individuals.